PENGARUH KEPEMILIKAN INSTITUSIONAL DAN PROFITABILITAS TERHADAP NILAI PERUSAHAAN DENGAN MANAJEMEN LABA SEBAGAI VARIABEL INTERVENING ( STUDI EMPIRIS PADA PERUSAHAAN PERBANKAN YANG TERDAFTAR DI BEI PERIODE 2010-2014 ) - Ramashar, Wira; Zulbahridar, Zulbahridar (Fakultas Ekonomi dan Bisnis, Universitas Riau, 2016)
This study aimed to analyze and explain: (1) the influence of institutionalownership on firm value, (2) the influence of institutional ownership on firm valuethrough earnings management, (3) the effect of profitability on firm value, (4) theeffect of profitability on firm value through management earnings, (5) the effect ofearnings management on firm value. The study population was bankingcompanies listed in the Indonesia Stock Exchange (BEI) in the period 2010 to2014 with a total sample of 26 companies. Technical analysis of the data in thisstudy using path analysis with SPSS version 21.Results of data analysis proves that : (1) institutional ownership has no effect onfirm value, (2) institutional ownership positively affects the firm value to bemediated by earnings management, (3) profitability negatively affect the firmvalue, (4) profitability negatively affect the firm value to be mediated by earningsmanagement (5) earnings management negatively affect the firm value.